Effectiveness of Blood Learning Based on the Ethnochemical Approach Module on Improving Science Literation Abilities - Seprianto Seprianto; Molani Paulina Hasibuan (Budapest International Research and Critics University, 2021)
The purpose of this study was to determine the effectiveness of module-based online learning with an ethnochemical approach in improving students' scientific literacy skills. This research is a quasi-experimental study with a pretest-posttest nonequivalent control group design. The study population was students of the Faculty of Teacher Training and Education, Samudra University who were taking basic chemistry courses. The results showed an increase in science literacy skills based on the N-gain value in the experimental class of 0.54 in the medium category and 0.33 in the control class who were also in the medium category. Analysis with t test based on the posttest value obtained sig. (2-tailed) 0.030 or <0.05, which indicates a significant difference in the posttest scores of the two classes. Based on these two Kés, it can be concluded that module-based online learning with an ethnochemical approach is effective for improving students' scientific literacy skills. The results showed an increase in science literacy skills based on the N-gain value in the experimental class of 0.54 in the medium category and 0.33 in the control class who were also in the medium category. Analysis with t test based on the posttest value obtained sig. (2-tailed) 0.030 or <0.05, which indicates a significant difference in the posttest scores of the two classes. Based on these two Kés, it can be concluded that module-based online learning with an ethnochemical approach is effective for improving students' scientific literacy skills. The results showed an increase in science literacy skills based on the N-gain value in the experimental class of 0.54 in the medium category and 0.33 in the control class who were also in the medium category. Analysis with t test based on the posttest value obtained sig. (2-tailed) 0.030 or <0.05, which indicates a significant difference in the posttest scores of the two classes. Based on these two Kés, it can be concluded that module-based online learning with an ethnochemical approach is effective for improving students' scientific literacy skills.